How we are portrayed, is that what we are? - Cristina Fernández García; María Lorena Pérez López (Cultura de los Cuidados, 2012)
Descriptive study using literature and digital material as sources, its aim is to analyse the perception society has of nursing and the role nurses play in daily life. The scarce impact of our profession as authors of dissemination articles in the field of Health Education is a fact. So is the romantic or frivolous view of Nursing that current literature and mass media offer, as a reflection of common public opinion.